Auroral Beads in Conjunction With Kinetic Alfvén Waves in the Equatorial Inner‐Magnetosphere. Issue 9 (10th May 2022) - Tian, S.; Lyons, L. R.; Nishimura, Y.; Wygant, J. R.; Lysak, R. L.; Ferradas, C. P.; An, X.; Igl, A. B.; Reeves, G. D.; Larsen, B. A.; Ma, D.
Abstract: Auroral beads are spatially wavy forms routinely seen before the onset of auroral substorms and are closely related to the onset‐related instabilities. To date, the acceleration mechanism of electrons that create auroral beads is not fully determined. Here, we present a fortuitous event when the Van Allen Probe A (RBSP‐A) was in magnetic conjunction with auroral beads. RBSP‐A observed Alfvén waves, locally generated kinetic Alfvén waves (KAWs) and Alfvénic accelerated electrons at several 100 eV. The Alfvén waves and KAWs carried sufficient Poynting flux to power visible aurora and may control the beads' motion. These observations and previous simulations support that the Alfvénic acceleration is the acceleration mechanism of the auroral beads. Specifically, KAWs are generated around the equator and accelerate local cold electrons to several 100 eV. The waves are suggested to propagate to both hemispheres and accelerate electrons to several keV, which directly account for the auroral beads. Plain Language Summary: Auroral display in the ionosphere is part of a complicated energy release process called the geomagnetic substorm. During substorms, auroral beads, a type of spatially wavy aurora, appear and then suddenly brighten and expand in local time and latitude. Because auroral beads are routinely seen before the sudden brightening and expansion, they are widely studied to understand why aurora evolves in such an explosive way. To date, it is generally accepted that auroral beads map to a source region in the equatorial plasma in space where waves and plasma instabilities occur. It is also known that the auroral beads are directly caused by electrons of keV energy precipitating into the ionosphere. However, how these electrons are accelerated along the magnetic field lines from the source region to the ionosphere is unknown. Here, we analyze the wave and plasma data measured by the Van Allen Probe A satellite when auroral beads occurred. We find that a type of low frequency wave, called the kinetic Alfvén wave, is generated within the source region and can accelerate local electrons to several 100 eV energy and can potentially further accelerate these electrons to keV to trigger auroral beads. Key Points: Observations support kinetic Alfvén waves (KAWs) as the acceleration mechanism for auroral beads KAWs were generated around the equator where local plasma convection matched beads' azimuthal motion KAW accelerated electrons were observed and further Alfvénic acceleration might occur down to 2 Re altitude